Preparation method of active contact antibacterial coating on titanium alloy surface
By forming an antibacterial coating with a semi-coated structure of MoS2 and BaTiO3 on the surface of the titanium alloy, combining photothermal and piezoelectric effects, the poor antibacterial effect and ion release problems in the prior art are solved, and efficient bacterial antibacterial effect is achieved. Avoid silver ion toxicity.
Patent Information
- Application Number
- CN202410166936.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-06
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-02-06
AI Technical Summary
The antibacterial coating on the surface of existing titanium alloys has poor antibacterial effect, and there is toxicity of silver ion release to human organs. The ion release is not long-term, and the photocatalytic bactericidal effect is limited, especially when the bacterial concentration is high, the effect is slow.
By synthesizing a titanium dioxide nanotube precursor containing a molybdenum source on the surface of the titanium alloy, hydrothermal reaction is carried out to generate MoS2 nanosheets, and hydrothermal reaction is carried out in Ba(OH)2 solution to form active contact between MoS2 and BaTiO3 semi-coated structures. Antibacterial coatings, which capture bacteria using photothermal and photocatalytic combined with piezoelectric effect.
The firm combination of MoS2 and BaTiO3 composite coating is achieved, and the antibacterial effect is enhanced through bonding and chimeric methods is enhanced. The photothermal and piezoelectric effects are used to actively contact bacteria, achieving efficient antibacterial effect without releasing ions, which improves the antibacterial coating. stability and antibacterial rate.
Smart Images

Figure CN118147620B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of antibacterial materials on titanium alloy surfaces, and in particular relates to a method for preparing an active contact antibacterial coating on the surface of a titanium alloy. Background Art
[0002] Titanium alloys are widely used in daily life and medicine because of their light weight, high specific strength and corrosion resistance. If titanium alloy products are exposed to a humid environment for a long time, bacterial colonies will form on their surface. In the medical field, titanium alloys are often used as implants, but titanium and titanium alloys themselves do not have antibacterial properties. After being implanted in the human body, the adhesion proteins and fibrin adsorbed on their surfaces will form a protein film, which creates favorable conditions for the adhesion of pathogens, allowing bacteria to continue to multiply on the surface of the implant to form a biofilm. These bacteria (such as Staphylococcus aureus) introduced during surgery or in other ways often have strong drug resistance and can lead to persistent infection of the implant. Therefore, the research on coatings with antibacterial effects on the surface of titanium alloys is widely needed and of great significance.
[0003] Chinese patent (application number: 201710083747.1, publication number: 106924810A, publication date: 2019-11-22) discloses an antibacterial coating material loaded with silver nanoparticles on the surface of titanium alloy and its preparation method, forming a tannic acid-iron film on the surface of titanium alloy, and then using silver ammonia complex solution and titanium alloy sheet to stir on a magnetic stirrer to obtain an antibacterial coating loaded with silver nanoparticles on the surface of titanium alloy. However, as an implant, due to the release of silver ions, it will form ion accumulation if it exists for a long time, which will be toxic to human organs. Chinese patent (application number: 201010130657.1, publication number: 101791433A, publication date: 2012-11-14) discloses a method for preparing a coating, firstly growing a layer of molecular sieve film on the surface of pure titanium or titanium alloy, using ion exchange technology to load a certain amount of inorganic antibacterial ions on the molecular sieve layer, and slowly releasing ions to obtain a surface coating with antibacterial properties. However, the released ions cannot provide long-term antibacterial effects. As a medical titanium antibacterial material, the release of antibacterial ions will also increase the burden on organs. A Chinese patent (application number: 201710858562.3, publication number: 107760069A, publication date: 2019-09-24) discloses a light-excited silver phosphate / graphene oxide composite antibacterial coating, which is grown on the surface of a porous rough titanium sheet by mixing silver phosphate and graphene oxide. However, the effect of photocatalytic sterilization is limited, and when the bacterial concentration is high, the photocatalytic sterilization effect is slow. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an active contact antibacterial coating on a titanium alloy surface, so as to solve the problem that the existing coating has poor antibacterial effect.
[0005] The technical solution adopted by the present invention is a method for preparing an active contact antibacterial coating on a titanium alloy surface, which is specifically implemented according to the following steps:
[0006] Step 1, synthesizing a titanium dioxide nanotube precursor containing a molybdenum source on the surface of a titanium alloy;
[0007] Step 2, placing the titanium alloy sample obtained in step 1 in a sulfur source mixed solution, placing it in a hydrothermal reactor for hydrothermal reaction, washing and drying, and generating MoS2 nanosheets rooted in titanium dioxide nanotubes;
[0008] Step 3, placing the titanium alloy sample obtained in step 2 in a Ba(OH)2 solution, and placing it in a hydrothermal reactor for hydrothermal reaction, cooling, cleaning, drying, and polarizing, an active contact antibacterial coating with a semi-coated structure of MoS2 and BaTiO3 can be prepared on the surface of the titanium alloy.
[0009] The present invention is also characterized in that:
[0010] In step 1, specifically:
[0011] Step 1.1, after cleaning and degreasing the titanium alloy, immerse it in a chemical polishing solution for chemical polishing treatment until no bubbles are generated in the polishing solution, then clean and dry it to obtain a pretreated titanium alloy.
[0012] Step 1.2, placing the titanium alloy obtained after step 1.1 on the anode of the anodizing workbench, using aluminum foil as the cathode, using a mixture of ethylene glycol, deionized water and ammonium fluoride as the electrolyte, performing two anodizing operations at a voltage of 20 to 60 V, cleaning, drying, and annealing, placing the obtained titanium alloy sample in a mixture containing a molybdenum source, and vacuum drying, thereby synthesizing a titanium dioxide nanotube precursor containing a molybdenum source on the surface of the titanium alloy.
[0013] In step 1.1, the chemical polishing solution is composed of nitric acid, hydrofluoric acid and deionized water in a volume ratio of 4:1:5.
[0014] In step 1.2, the anodization time is 1 to 2 hours; during the first anodization, the mass ratio of ethylene glycol, deionized water and ammonium fluoride in the electrolyte is 200:5:1; during the second anodization, the mass ratio of ethylene glycol, deionized water and ammonium fluoride in the electrolyte is 500:20:1.
[0015] In step 1.2, the molybdenum source mixed solution is prepared by mixing a molybdenum source compound and deionized water in a mass ratio of 1 to 3:50 to 60; the molybdenum source compound is ammonium tetramolybdate or ammonium paramolybdate.
[0016] In step 1.2, the annealing temperature is 300-500° C., and the annealing time is 1-5 h; the vacuum drying temperature is 50-60° C., and the time is 6-8 h.
[0017] In step 2, the preparation process of the sulfur source mixed solution is: uniformly mix the sulfur source compound and deionized water in a mass ratio of 1 to 6:25 to 60, then add HCl to adjust the pH of the solution to 1 to 3 to obtain a sulfur source mixed solution; the sulfur source compound is thiourea or thioacetamide; the hydrothermal reaction temperature is 200 to 280° C., and the hydrothermal reaction time is 6 to 12 hours.
[0018] In step 3, the concentration of the Ba(OH)2 solution is 0.3-0.5 mol / L.
[0019] In step 3, the hydrothermal reaction temperature is 200-220° C., the hydrothermal reaction time is 2-3 h; the polarization voltage is 20-60 V, and the polarization time is 1-2 h.
[0020] The beneficial effects of the present invention are:
[0021] (1) The in-situ grown BaTiO3 and MoS2 form a semi-encapsulated structure. Through bonding and intercalation, the lamellar MoS2 can grow more firmly on the surface of the titanium sheet, making the coating less likely to fall off, and the sharp edge of MoS2 can better puncture bacteria to achieve an antibacterial effect;
[0022] (2) The composite coating of BaTiO3 and MoS2 utilizes photothermal and photocatalytic sterilization, and combines with the piezoelectric effect to form an electric field on the surface of titanium alloy to adsorb or isolate electrically charged bacteria, actively contacting and killing bacteria to achieve an antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic structural diagram of the active contact antibacterial coating on the titanium alloy surface of the present invention. Specific implementation methods
[0024] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0025] The method for preparing the active contact antibacterial coating on the surface of titanium alloy of the present invention is specifically implemented according to the following steps:
[0026] Step 1, synthesizing a titanium dioxide nanotube precursor containing a molybdenum source on the surface of a titanium alloy; specifically:
[0027] Step 1.1, after cleaning and degreasing the titanium alloy, immersing it in a chemical polishing solution for chemical polishing, until no bubbles are generated in the polishing solution, then cleaning and drying to obtain a pretreated titanium alloy;
[0028] The chemical polishing solution is composed of nitric acid, hydrofluoric acid and deionized water in a volume ratio of 4:1:5;
[0029] Step 1.2, placing the titanium alloy obtained after step 1.1 on the anode of the anodizing workbench, using aluminum foil as the cathode, using a mixed solution of ethylene glycol, deionized water and ammonium fluoride as the electrolyte, performing two anodizing operations at a voltage of 20 to 60 V, cleaning, drying, and annealing, placing the obtained titanium alloy sample in a mixed solution containing a molybdenum source, and vacuum drying, thereby synthesizing a titanium dioxide nanotube precursor containing a molybdenum source on the surface of the titanium alloy;
[0030] The anodizing time is 1 to 2 hours; the annealing temperature is 300 to 500°C, and the annealing time is 1 to 5 hours;
[0031] During the first anodization, the mass ratio of ethylene glycol, deionized water, and ammonium fluoride in the electrolyte was 200:5:1;
[0032] During the second anodization, the mass ratio of ethylene glycol, deionized water and ammonium fluoride in the electrolyte was 500:20:1;
[0033] The molybdenum source mixed solution is prepared by mixing a molybdenum source compound and deionized water in a mass ratio of 1-3:50-60; the molybdenum source compound is ammonium tetramolybdate or ammonium paramolybdate.
[0034] The vacuum drying temperature is 50-60°C and the time is 6-8 hours.
[0035] Step 2, placing the titanium alloy sample obtained in step 1 in a sulfur source mixed solution, and placing it in a hydrothermal reactor for hydrothermal reaction, after cooling to room temperature, taking it out, flushing the residual solvent on the surface with ethylene glycol, and then washing and drying, to generate MoS2 nanosheets rooted in titanium dioxide nanotubes;
[0036] The preparation process of the sulfur source mixed solution is as follows: a sulfur source compound and deionized water are mixed evenly at a mass ratio of 1 to 6:25 to 60, and then HCl is added to adjust the pH of the solution to 1 to 3 to obtain a sulfur source mixed solution; and the sulfur source mixed solution is added to 2 / 3 of the hydrothermal reactor;
[0037] The sulfur source compound is thiourea or thioacetamide.
[0038] The hydrothermal reaction temperature is 200-280°C, and the hydrothermal reaction time is 6-12h;
[0039] Step 3, preparing an active contact antibacterial coating with a semi-encapsulated structure of MoS2 and BaTiO3;
[0040] Specifically, the titanium alloy sample obtained in step 2 is placed in a Ba(OH)2 solution, and placed in a hydrothermal reactor for hydrothermal reaction, cooled, cleaned, dried, and polarized to prepare an active contact antibacterial coating with a semi-coated structure of MoS2 and BaTiO3 on the surface of the titanium alloy.
[0041] The concentration of Ba(OH)2 solution is 0.3~0.5mol / L;
[0042] The hydrothermal reaction temperature is 200-220°C, the hydrothermal reaction time is 2-3h; the polarization voltage is 20-60V, and the polarization time is 1-2h;
[0043] Figure 1 It is a structural schematic diagram of the active contact antibacterial coating on the surface of titanium alloy of the present invention; the active contact antibacterial coating prepared on the surface of titanium alloy by anodizing method combined with hydrothermal method is mainly composed of barium titanate nanotubes with piezoelectric effect and molybdenum disulfide nanosheets with photothermal and photocatalytic properties. Barium titanate can be generated by in-situ reaction of titanium dioxide nanotubes, which can not only retain the nanotube structure but also ensure the strong bonding between the two. Molybdenum disulfide nanosheets are synthesized on the surface of titanium alloy by hydrothermal method. In the preparation process, titanium dioxide nanotubes are first formed on the surface of titanium alloy, and molybdenum disulfide nanosheets rooted in nanotubes are generated on the surface of titanium alloy after a hydrothermal reaction. After the secondary hydrothermal reaction, barium titanate is in-situ generated on the titanium dioxide nanotubes, and finally forms a semi-encapsulated structure with molybdenum disulfide nanosheets. Molybdenum disulfide and barium titanate are firmly combined together by bonding and intercalation, and the antibacterial coating is not easy to fall off.
[0044] Example 1
[0045] After cleaning and degreasing the titanium alloy, it is immersed in a chemical polishing solution for chemical polishing to obtain a titanium alloy. After no bubbles are generated in the polishing solution, it is cleaned and dried for use. Ethylene glycol, deionized water, and ammonium fluoride are mixed in a mass ratio of 200:5:1 to prepare a mixed solution. The titanium alloy is placed on the anode of the anodizing workbench, and the aluminum foil is used as the cathode for the first anodizing at a voltage of 20V. After oxidation for 2 hours, it is cleaned and dried. Then, ethylene glycol, deionized water, and ammonium fluoride in a mass ratio of 500:20:1 are configured into an electrolyte for the second anodizing, and then cleaned and dried. The treated titanium alloy containing nanotubes is annealed at 300°C for 5 hours, and the obtained titanium alloy sample is mixed with 0.8g of (NH4)6Mo7O 24The mixture of 4H2O and deionized water was vacuum dried at 50℃ for 8h. The sample was mixed with 50mL deionized water and 1.52g CH4N2S to make a pH=1 mixture, which was hydrothermally heated at 200℃ for 12h and then washed and dried. The treated sample was heated with a 0.3mol / L barium hydroxide solution at 200℃ for 3h. Finally, the active contact antibacterial coating on the titanium alloy surface was obtained by polarization at 20V for 2h.
[0046] Example 2
[0047] After cleaning and degreasing the titanium alloy, it is immersed in a chemical polishing solution for chemical polishing to obtain a titanium alloy. After no bubbles are generated in the polishing solution, it is cleaned and dried for use. A mixed solution is prepared by mixing ethylene glycol, deionized water and ammonium fluoride in a mass ratio of 200:5:1. The titanium alloy is placed on the anode of the anodizing workbench, and the aluminum foil is used as the cathode for the first anodizing at a voltage of 60V. After oxidation for 1 hour, it is cleaned and dried. Then, ethylene glycol, deionized water and ammonium fluoride in a mass ratio of 500:20:1 are mixed into an electrolyte for the second anodizing, and then cleaned and dried. The treated titanium alloy containing nanotubes is annealed at 500°C for 1 hour. The obtained titanium alloy sample is mixed with 0.8g of (NH4)6Mo7O 24 ·The mixture of 4H2O and deionized water was vacuum dried at 60℃ for 6h. The sample was mixed with 50ml of deionized water and 1.52g of CH4N2S to make a pH=3 mixture, which was hydrothermally heated at 280℃ for 6h and then washed and dried. The treated sample was heated with a 0.5mol / L barium hydroxide solution at 220℃ for 2h. Finally, the active contact antibacterial coating on the titanium alloy surface was obtained by polarization at 60V for 1h.
[0048] Example 3
[0049] After cleaning and degreasing the titanium alloy, it is immersed in a chemical polishing solution for chemical polishing to obtain a titanium alloy. After no bubbles are generated in the polishing solution, it is cleaned and dried for use. A mixed solution is prepared by mixing ethylene glycol, deionized water and ammonium fluoride in a mass ratio of 200:5:1. The titanium alloy is placed on the anode of the anodizing workbench, and the aluminum foil is used as the cathode for the first anodizing at a voltage of 20V. After oxidation for 2 hours, it is cleaned and dried. Then, ethylene glycol, deionized water and ammonium fluoride in a mass ratio of 500:20:1 are mixed into an electrolyte for the second anodizing, and then cleaned and dried. The treated titanium alloy containing nanotubes is annealed at 300°C for 5 hours. The obtained titanium alloy sample is mixed with 0.5g of (NH4)2Mo4O 13·The mixture of 2H2O and deionized water was vacuum dried at 50℃ for 8h. The sample was mixed with 50ml of deionized water and 0.9g of CH4N2S to make a pH=1 mixture, which was hydrothermally treated at 200℃ for 12h and then washed and dried. The treated sample was heated with a 0.3mol / L barium hydroxide solution at 200℃ for 3h. Finally, the active contact antibacterial coating on the titanium alloy surface was obtained by polarization at 20V for 2h.
[0050] Example 4
[0051] After cleaning and degreasing the titanium alloy, it is immersed in a chemical polishing solution for chemical polishing to obtain a titanium alloy. After no bubbles are generated in the polishing solution, it is cleaned and dried for use. A mixed solution is prepared by mixing ethylene glycol, deionized water and ammonium fluoride in a mass ratio of 200:5:1. The titanium alloy is placed on the anode of the anodizing workbench, and the aluminum foil is used as the cathode for the first anodizing at a voltage of 60V. After oxidation for 1 hour, it is cleaned and dried. Then, ethylene glycol, deionized water and ammonium fluoride in a mass ratio of 500:20:1 are mixed into an electrolyte for the second anodizing, and then cleaned and dried. The treated titanium alloy containing nanotubes is annealed at 500°C for 1 hour. The obtained titanium alloy sample is mixed with 0.5g of (NH4)2Mo4O 13 ·The mixture of 2H2O and deionized water was vacuum dried at 60℃ for 6h. The sample was mixed with 50ml of deionized water and 0.9g of CH4N2S to make a pH=3 mixture, which was hydrothermally heated at 280℃ for 6h and then washed and dried. The treated sample was heated with a 0.5mol / L barium hydroxide solution at 220℃ for 2h. Finally, the active contact antibacterial coating on the titanium alloy surface was obtained by polarization at 60V for 1h.
[0052] Control group
[0053] After cleaning and degreasing the titanium alloy, it is immersed in a chemical polishing solution for chemical polishing to obtain a titanium alloy. After no bubbles are generated in the polishing solution, it is cleaned and dried for use. A mixed solution is prepared by mixing ethylene glycol, deionized water and ammonium fluoride in a mass ratio of 200:5:1. The titanium alloy is placed on the anode of the anodizing workbench, and the aluminum foil is used as the cathode for the first anodizing at a voltage of 40V. After oxidation for 2 hours, it is cleaned and dried. Then, ethylene glycol, deionized water and ammonium fluoride in a mass ratio of 500:20:1 are mixed into an electrolyte for the second anodizing and then cleaned and dried. The treated titanium alloy containing nanotubes is annealed at 400°C for 3 hours. The obtained titanium alloy sample is mixed with 0.8g of (NH4)6Mo7O 24·The mixture of 4H2O and deionized water was vacuum dried at 50℃ for 7h. The sample was mixed with 50ml deionized water and 1.52g CH4N2S to make a pH=2 mixture, which was hydrothermally heated at 240℃ for 6h and then washed and dried. The treated sample was heated with 0.3mol / L barium hydroxide solution at 200℃ for 3h to obtain the product.
[0054] After applying physiological load (the frequency is set to 3 Hz and the loaded force is 60 N to simulate the force and frequency of human bone), the active contact antibacterial coating on the titanium alloy surface prepared by Examples 1-4 of the present invention is subjected to non-polarization treatment and no physiological load is applied. Co-cultured with Escherichia coli and Staphylococcus aureus and irradiated with near-infrared light, the antibacterial rate results are shown in Table 1. It can be seen from Table 1 that the antibacterial rates of Examples 1-4 on Escherichia coli and Staphylococcus aureus when applying physiological loads are all above 98%. The antibacterial rate of the control group when no physiological load is applied is above 90%. In comparison, the antibacterial effect of the active contact antibacterial coating on the titanium alloy surface synthesized by the present invention is better.
[0055] Table 1 Antibacterial rate of co-culture of Escherichia coli and Staphylococcus aureus in Examples 1-4 and the control group
[0056] Staphylococcus aureus inhibition rate / % Escherichia coli inhibition rate / % Example 1 99.4 99.2 Example 2 99.8 99.1 Example 3 99.2 98.7 Example 4 98.5 99.1 Control group 90.1 91.8
[0057] The active contact antibacterial coating on the titanium alloy surface of the present invention, the semi-encapsulated structure of MoS2 and BaTiO3 can improve the combination of the titanium alloy and the antibacterial coating, and the piezoelectric synergy of BaTiO3 is utilized without releasing ions, actively contacting and capturing bacteria and combining the photothermal and photocatalytic properties of MoS2 for synergistic antibacterial. As can be seen from Table 2, the piezoelectric coefficient of the active contact antibacterial coating on the titanium alloy surface prepared in Examples 1-4 can reach 1.5pC / N, indicating that the coating has a piezoelectric effect, which can form a surface piezoelectric charge on the coating surface under the stimulation of mechanical energy. This piezoelectric charge can affect the adhesion of bacteria, forming an active contact antibacterial system. The active contact antibacterial coating on the titanium alloy surface of Examples 1-4 and the pure titanium group were irradiated with a near-infrared laser for 5 minutes, and the temperature changes were observed. The results are shown in Table 2. It can be seen from the table that compared with the pure titanium group, the active contact antibacterial coatings on the titanium alloy surfaces of Examples 1-4 have better photothermal conversion performance. After 5 minutes of irradiation, the surface temperature can reach above 41.8°C, indicating that the active contact antibacterial coatings on the titanium alloy surfaces prepared in Examples 1-4 have photothermal conversion performance. The temperature of the coating surface can be increased by irradiation with near-infrared light, thereby inhibiting the proliferation and adhesion of bacteria.
[0058] Table 2 Piezoelectric coefficients of the antibacterial coatings of Examples 1-4 and temperatures after infrared irradiation
[0059] project Piezoelectric coefficient / (pC / N) Temperature / ℃ Example 1 1.8 43.1 Example 2 1.5 41.8 Example 3 1.3 43.5 Example 4 2.1 42.3 Pure titanium group 0 26.2
Claims
1. A method for preparing an active contact antibacterial coating on a titanium alloy surface, characterized in that: Follow the steps below to implement it: Step 1, synthesizing a titanium dioxide nanotube precursor containing a molybdenum source on the surface of a titanium alloy; specifically: Step 1.1, after cleaning and degreasing the titanium alloy, immersing it in a chemical polishing solution for chemical polishing, until no bubbles are generated in the polishing solution, then cleaning and drying to obtain a pretreated titanium alloy; Step 1.2, placing the titanium alloy obtained after step 1.1 on the anode of the anodizing workbench, using aluminum foil as the cathode, using a mixture of ethylene glycol, deionized water and ammonium fluoride as the electrolyte, performing two anodizing operations at a voltage of 20 to 60 V, cleaning, drying, and annealing, placing the obtained titanium alloy sample in a mixture containing a molybdenum source, and vacuum drying, thereby synthesizing a titanium dioxide nanotube precursor containing a molybdenum source on the surface of the titanium alloy; The molybdenum source mixed solution is prepared by mixing a molybdenum source compound and deionized water in a mass ratio of 1-3:50-60; the molybdenum source compound is ammonium tetramolybdate or ammonium paramolybdate; Step 2, placing the titanium alloy sample obtained in step 1 in a sulfur source mixed solution, placing it in a hydrothermal reactor for hydrothermal reaction, washing and drying, and generating MoS2 nanosheets rooted in titanium dioxide nanotubes; The preparation process of the sulfur source mixed solution is as follows: uniformly mixing the sulfur source compound and deionized water in a mass ratio of 1-6:25-60, then adding HCl to adjust the pH value of the solution to 1-3 to obtain the sulfur source mixed solution; the sulfur source compound is thiourea or thioacetamide; the hydrothermal reaction temperature is 200-280°C, and the hydrothermal reaction time is 6-12 h; Step 3, placing the titanium alloy sample obtained in step 2 in a Ba(OH)2 solution, the concentration of the Ba(OH)2 solution is 0.3~0.5 mol / L; and placing it in a hydrothermal reactor for hydrothermal reaction, cooling, cleaning, drying, and polarizing, to prepare an active contact antibacterial coating with a semi-coated structure of MoS2 and BaTiO3 on the surface of the titanium alloy.
2. The method for preparing the active contact antibacterial coating on the titanium alloy surface according to claim 1, characterized in that: In the step 1.1, the chemical polishing solution is composed of nitric acid, hydrofluoric acid and deionized water in a volume ratio of 4:1:
5.
3. The method for preparing the active contact antibacterial coating on the titanium alloy surface according to claim 1, characterized in that: In the step 1.2, the anodization time is 1-2 hours; during the first anodization, the mass ratio of ethylene glycol, deionized water and ammonium fluoride in the electrolyte is 200:5:1; during the second anodization, the mass ratio of ethylene glycol, deionized water and ammonium fluoride in the electrolyte is 500:20:
1.
4. The method for preparing the active contact antibacterial coating on the titanium alloy surface according to claim 1, characterized in that: In the step 1.2, the annealing temperature is 300-500° C., and the annealing time is 1-5 hours; the vacuum drying temperature is 50-60° C., and the time is 6-8 hours.
5. The method for preparing the active contact antibacterial coating on the titanium alloy surface according to claim 1, characterized in that: In step 3, the hydrothermal reaction temperature is 200-220° C., the hydrothermal reaction time is 2-3 h; the polarization voltage is 20-60 V, and the polarization time is 1-2 h.
Citation Information
Patent Citations
Molecular sieve antibacterial coating with pure titanium or titanium alloy surface and preparation method thereof
CN101791433A
Nanometer antibacterial coating material based on nanometer silver particles and preparation method of nanometer antibacterial coating material
CN106924810A
Preparation method and application of light excited-silver phosphate / graphene oxide composite antibacterial coating layer
CN107760069A
Molybdenum disulfide-loaded titania nanotube and synthetic method thereof
CN104894627A
Preparation method of chitosan / molybdenum disulfide photocatalytic anti-microbial coating
CN106917131A
